2007
DOI: 10.1007/s00244-005-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Metals in Water, Sediment, Biofilm, Benthic Macroinvertebrates, and Fish in the Boulder River Watershed, Montana, and the Role of Colloids in Metal Uptake

Abstract: To characterize the partitioning of metals in a stream ecosystem, concentrations of trace metals including As, Cd, Cu, Pb, and Zn were measured in water, colloids, sediment, biofilm (also referred to as aufwuchs), macroinvertebrates, and fish collected from the Boulder River watershed, Montana. Median concentrations of Cd, Cu, and Zn in water throughout the watershed exceeded the U.S. EPA acute and chronic criteria for protection of aquatic life. Concentrations of As, Cd, Cu, Pb, and Zn in sediment were suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 24 publications
2
63
0
Order By: Relevance
“…Fish are exposed to heavy metals both directly from water and sediment and indirectly through the food chain, especially Cu, Cd, and Zn [19]. Heavy metal bioaccumulation affects the structure and function of fish vital organs.…”
Section: Discussionmentioning
confidence: 99%
“…Fish are exposed to heavy metals both directly from water and sediment and indirectly through the food chain, especially Cu, Cd, and Zn [19]. Heavy metal bioaccumulation affects the structure and function of fish vital organs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, previous studies have reported significant correlations between Cu and Zn concentrations in water and biofilms in polluted stream ecosystems of Montana, where concentrations of the heavy metals were significantly higher than those in the , right set of canonical variables) and taxonomic composition of algal community (% of a given group in total biomass of epilithic microalgae, right set of canonical variables). See Table 2 Yenisei River [4]. Using pooled data from unpolluted and polluted sites, a significant correlation was found between Cu and Zn contents in water and in periphyton in the Birs River, but there were no such correlations for the Thur River with only background levels of metals [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, the content of a metal in water, especially in rivers with a high flow velocity, may reflect only short-term events and does not necessarily mean that biota and sediments are polluted with the metal [1,2]. Thus, periphyton (benthic algal assemblages, also referred to as biofilms) is often used to monitor chronic metal pollution in rivers, since periphytic organisms can accumulate metals from ambient water and sediments in their biomass [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Bottom sediments have similar properties as biofilms regarding the cycling and fate of pollutants in the aquatic environment: they have the ability to bind different substances, can act as a feeding source for macroinvertebrates or fish, can act as secondary sources of pollution during floods as well as low-water periods, and are a more or less temporal sink for pollutants (e.g., Baudo et al 1990;Lotufo 1998;Gewurtz et al 2000;Baborowski et al 2004;Stachel et al 2004;Umlauf et al 2005). Pollutants accumulated in both biofilms and sediments can be considered bioavailable (e.g., Landrum and Robbins 1990;Farag et al 2007).…”
Section: Introductionmentioning
confidence: 98%